PEER FEEDBACK STRATEGY TOWARDS SIXTH SEMESTER STUDENTS’ ABILITY IN TRANSLATION - S, K. Dedy Sandiarsa; Suhaili, Muhamad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This Research aimed at finding the effect of Peer Feedback strategy towards fifth semester students’ ability in translation subject at S1 Degree of English Department FBMB, Mandalika University. This research was quasi experimental design of experimental research. The population was 3 classes (118 students), in which 2 classes were selected as the sample that was divided into two groups; Class A with 30 students as the experimental group and Class B with 30 students as the control, the groups were divided by using Simple Random Sampling technique. The data collection got from translation test of translating texts given, then the data were analyzed by using SPSS 2019 computer program for windows 10. The result showed that the significant value of = 0.000 was lower than 0.05. Therefore, it can be concluded that the students in Class A who were taught by using Peer Feedback strategy have higher score in translation than the students of Class B who were taught by using the grammar translation strategy. Based on the conclusion, the researcher suggested that Peer Feedback strategy should be used to teach translation for the fifth semester students at S1 degree of English Department of FBMB, Mandalika University.